The crystal chemistry of pumpellyite from Sugashima and julgoldite from Kouragahana, Japan: Toward a comprehensive understanding of the crystal chemistry of pumpellyite-group minerals - Daisuke NISHIO-HAMANE; Mariko NAGASHIMA (Journal of Mineralogical and Petrological Sciences, 2025)
Single-crystal X-ray crystal-structure refinements and electron-microprobe analyses of julgoldite from Kouragahana, Shimane Peninsula, and pumpellyite from Sugashima, Mie, Japan yielded the compositions of WCa2.00X(Fe0.69Mg0.20Al0.11)Σ1.00Y(Fe3+1.46Al0.54)Σ2.00Si3.00O14−n(OH)n and WCa2.00X(Al0.56Mg0.35Fe0.09)Σ1.00YAl2.00Si3.00O14−n(OH)n (4 ≥ n ≥ 3), respectively. The latter was classified as pumpellyite-(Al), while the former can only be concluded to be either julgoldite-(Fe3+) or julgoldite-(Fe2+). The hydroxyl groups determined by structure refinement are consistent with those known for pumpellyite. The length of the b-axis most accurately reflects the average size of ionic radii at the Y site based on structural and chemical data for pumpellyite-group minerals. In contrast, the lengths of the a- and c-axes demonstrate a favorable correlation with the mean ionic radius of the Y site; however, they exhibit greater dispersion compared to the b-axis. This is attributed to the lateral expansion or shrinkage of the (010) plane caused by variation in the size of the X site. Therefore, the pumpellyite group minerals with longer a- and c-axes may be rich in divalent cations at the X site. The well-defined, intense Raman peak around 695 cm−1 is characteristic of pumpellyite-group minerals and is likely attributed to the Si-O-Si bending mode. The six to seven Raman peaks resulting from O-H bond stretching reflect the complex hydrogen bond system in the pumpellyite group structure, arising from the presence of multiple hydroxyl groups and variations in the local chemical environment due to compositional differences.